SCRUM: FLEXIBILITY WITHIN A RIGID FRAMEWORKS - R. Andreeva; O. Sinyaeva (Вестник университета)
Nowaday, traditional methods of project management are becoming obsolete, which is why it is necessary to introduce modern flexible methodologies into all spheres of life, one of which is Scrum, which improves the efficiency and productivity of the work as a whole. The article presents the basic principles of Scrum, a study of the experience of implementing this methodology in Google, the Washington Information Service, the Information and Analytical Center of St. Petersburg, the Administration of the Head of the Republic of Sakha (Yakutia) and the Government of the Republic of Sakha (Yakutia), and in one of the schools of the Dutch city Alphen-an-den-Rijn.